The Role of Guidance and Counseling Teachers in Improving Discipline in Generation Z - Siska Aprelyani (Siber International Journal of Sport Education, 2024)
The Role of Guidance and Counseling Teachers for Generation Z. The aim is to analyze whether guidance and counseling teachers can play a role in improving discipline in generation Z. The method of writing this scientific article is by using the library research method, which is sourced from online media such as Google Scholar, Mendeley, and other online media. The results of this study are: 1) Guidance and Counseling Teachers play a role in Generation Z; 2) Discipline plays a role in Generation Z, 3) Guidance and Counseling Teachers play a role in improving Discipline in Generation Z. Apart from these 2 exogenous variables that influence the endogenous variables of Generation Z, there are many other factors including the principal, quality of education, curriculum.